The Naphthalene Catabolic Genes of Pseudomonas putida BS3701: Additional Regulatory Control - Pozdnyakova-Filatova, Irina; Petrikov, Kirill; Vetrova, Anna; Frolova, Alina; Streletskii, Rostislav; Zakharova, Marina (Frontiers in Microbiology, 2020)
Pseudomonas microorganisms are used for bioremediation of soils contaminated with petroleum hydrocarbons. The widely varying concentration of available nitrogen and iron (Fe) in soils was shown to affect residual hydrocarbons in the course of biodegradation. Hydrocarbon catabolism consists in the formation of a small number of intermediate metabolites, thus bringing together the transformation pathways of various polynuclear aromatic hydrocarbons (PAHs). According to the literature, the regulation of expression of catabolic genes and specific transcription regulators may involve nucleoid-associated proteins, alternative sigma-factors, quorum sensing components, and small RNAs, yet no comprehensive picture of catabolism of a certain PAH at all regulatory levels in the context of a certain macro- or microelement has been defined. The Pseudomonas putida strain BS3701 is a component of the “MicroBak” preparation for soil remediation. Previously, this strain was shown to contain genes encoding the key enzymes for naphthalene catabolism: naphthalene 1,2-dioxygenase, salicylate hydroxylase, catechol 2,3-dioxygenase, and catechol 1,2-dioxygenase. For the current study, this strain was cultivated in low nitrogen/low iron conditions with the concurrent evaluation of the activity of key enzymes of the naphthalene catabolic pathway and the mRNA level of genes encoding these enzymes. We are the first to report that naphthalene catabolic genes are subject not only to transcriptional but also post-transcriptional regulation.